Index of coordination in crawl technique at usual distances in training - Santos, P.; Rama, L. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION This study falls within the scope of the technical analysis in competitive swimming and is focused on using the Index of Coordination (IdC) developed by Didier Chollet et al (2000) to characterize the model of swimming synchronization. In this topic, published research always used official distances in the assessment protocols, never focusing on the different distances and tasks used during training sessions. Therefore, this study aimed to compare the coordinative model in the crawl technique at maximum speed in two different non-competitive distances, the 25m and the 300m, allowing coaches to have a better understanding of the tasks and the way swimmers swim during practice compared to the competition. METHODS The sample consisted of 8 male and 4 female athletes, averaging 17.04±3.78-year-old. Anthropometric data were collected. For the kinematic measurements, video recordings were done using 3 video cameras, one frontal and one laterally underwater and the last one laterally out of the water. Those records were analysed in Kinovea to obtain the following variables: velocity (v), stroke frequency (SF), stroke length (SL), swimming index (SI) and propulsive efficiency (eP). The lag time (LT) between the beginning of the propulsive phase of one arm and the end of the propulsive phase of the other arm was collected for the IdC, dividing this value by the total stroke time (Tt). Statistically, the normality and homogeneity of the distribution of all variables were analysed by the Shappiro-Wilk and Levene tests, respectively, requiring a significance of p = 0.05. RESULTS Average values of v, SF and SI decreased from 25 m to 300 m (1.77±0,17 m/s to 1,36± m/s ; 0,90±0,06 Hz to 0,62±0,05 Hz; 3,49±0,66 m2/s to 3,02±0,48 m2/s, respectively). But average values of SL and eP increased from 25 m to 300 m (1,96±0,18 m to 2,20±0,24 m; 17,91±1,68 % to 20,08±2,17 %, respectively). During IdC analyses, we observed that the values of all variables (LT, Tt and IdC) were higher at 25 m. On average, the athletes presented a coordination model in opposition on the 25 m (IdC = 0,57±3,14) and in superposition on the 300 m (IdC = -7,96 ± 3,56). DISCUSSION The athletes presented, on average, equal lag time between propulsive and non-propulsive phases on the 300 m, but different on the 25 m. As expected, athletes increased their IdC with increasing speed and decreasing distance, changing their coordination from superposition to opposition. The lower eP at 25 m is related to the overlapping of the propulsive phases, with no glide, perceived by the high IdC and shorter SL. On the 300 m, swimming in opposition allows greater glide with greater SL and smaller SF, leading to more efficient strokes, confirmed by the superior eP. All results were in line with former research using official distances and competition.